High Ambient Temperature Regulated the Plant Systemic Response to the Beneficial Endophytic Fungus Serendipita indica - Chen, Xiao-Jie; Yin, Yue-Qing; Zhu, Xin-Meng; Xia, Xue; Han, Jia-Jia (Frontiers in Plant Science, 2022)
Most plants in nature establish symbiotic associations with endophytic fungi in soil. Beneficial endophytic fungi induce a systemic response in the aboveground parts of the host plant, thus promoting the growth and fitness of host plants. Meanwhile, temperature elevation from climate change widely affects global plant biodiversity as well as crop quality and yield. Over the past decades, great progresses have been made in the response of plants to high ambient temperature and to symbiosis with endophytic fungi. However, little is known about their synergistic effect on host plants. The endophytic fungus Serendipita indica colonizes the roots of a wide range of plants, including Arabidopsis. Based on the Arabidopsis-S. indica symbiosis experimental system, we analyzed the synergistic effect of high ambient temperature and endophytic fungal symbiosis on host plants. By transcriptome analysis, we found that DNA replication-related genes were significantly upregulated during the systemic response of Arabidopsis aboveground parts to S. indica colonization. Plant hormones, such as jasmonic acid (JA) and ethylene (ET), play important roles in plant growth and systemic responses. We found that high ambient temperature repressed the JA and ET signaling pathways of Arabidopsis aboveground parts during the systemic response to S. indica colonization in roots. Meanwhile, PIF4 is the central hub transcription factor controlling plant thermosensory growth under high ambient temperature in Arabidopsis. PIF4 is also involving JA and/or ET signaling pathway. We found that PIF4 target genes overlapped with many differentially expressed genes (DEGs) during the systemic response, and further showed that the growth promotion efficiency of S. indica on the pif4 mutant was higher than that on the wild-type plants. In short, our data showed that high ambient temperature strengthened the growth promotion effect of S. indica fungi on the aboveground parts of the host plant Arabidopsis, and the growth promotion effect of the systemic response under high ambient temperature was regulated by PIF4.